“To This Day She Continues to Struggle with the Terror Imposed upon Her”: rape Narratives in Victim Impact Statements - Balfour, Gillian (Women & criminal justice, 2018)
This study locates the victim impact statements of raped women in the sociolegal context of significant sentencing law reforms introduced in Canada to address an ascendant victim’s rights movement. We examine 38 reported sentencing decisions in sexual assault cases in Ontario, Canada (1999-2010). Our objectives are to discern (a) whether the archetype of the ideal victim continues to influence juridical discourse after conviction and (b) what narratives of harm intersect with sentencing objectives and aggravating factors. Our findings suggest women express profound fear of re-victimization and traumatic effects of sexual violence regardless of the relational context of their rape experience. Most surprisingly, our data show sentencing judges view the sexual assault of an intoxicated rape victim as an aggravating factor. Future consideration for victim impact statements in sexual assault cases is discussed.